2018
DOI: 10.1080/10903127.2018.1428840
|View full text |Cite
|
Sign up to set email alerts
|

Acute Crisis Care for Patients with Mental Health Crises: Initial Assessment of an Innovative Prehospital Alternative Destination Program in North Carolina

Abstract: A dedicated community mental health center is able to treat patients experiencing acute mental health crises. LOS times were significantly shorter compared to regional EDs. Successful broader programmatic implementation could improve care quality and significantly reduce the volume of patients treated in the ED for acute mental health disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 6 publications
0
32
0
4
Order By: Relevance
“…These are patients with mental health issues and those affected by drugs and alcohol (Kleissl-Muir et al , 2018; Nikathil et al , 2017). Both presentations place a substantial burden on EDs, where workers do not always feel equipped to deal with these patients (Creed et al , 2018; Thomas et al , 2021). Furthermore, the ED is not deemed an appropriate environment for many of these patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are patients with mental health issues and those affected by drugs and alcohol (Kleissl-Muir et al , 2018; Nikathil et al , 2017). Both presentations place a substantial burden on EDs, where workers do not always feel equipped to deal with these patients (Creed et al , 2018; Thomas et al , 2021). Furthermore, the ED is not deemed an appropriate environment for many of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ED is not deemed an appropriate environment for many of these patients. They often wait for long periods of time in a highly stimulating environment, only to find that there are no suitable care pathways available to them (Creed et al , 2018; Thomas et al , 2021). In this context, we need to consider that for those with a mental health disorder, there is already a risk of stigmatisation, and these illnesses are associated with poorer health-care access and social marginalisation (Perry et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…– Community-based follow-up care: social work [ 55 120 121 122 ], home care nursing [ 56 121 ], diabetes clinics [ 79 80 ], falls prevention teams [ 75 77 ] and mental health facilities [ 57 59 123 124 125 ]…”
Section: Resultsmentioning
confidence: 99%
“…Even though a higher proportion of pediatric EMS calls are for low-acuity complaints than adult EMS calls, children have been excluded from the vast majority of community paramedicine programs 39 and other local initiatives that triage specific EMS calls to sites of care other than the ED. [40][41][42] A recent study found that 19% of all pediatric 911 calls in the US end with a caregiver refusal of transport. 43 This is substantially higher than the level of patient refusals for adults.…”
Section: Discussionmentioning
confidence: 99%